Computational techniques for multiphase flows - Yeoh, Guan Heng; Tu, Jiyuan (Butterworth-Heinemann, 2019)
The use of Computational Fluid Dynamics (CFD) has emerged as a powerful tool for the understanding of fluid mechanics in multiphase reactors, which are widely used in the chemical, petroleum, mining, food, beverage and pharmaceutical industries.